THE MOTHER'S PSYCHOLOGICAL RESPONSE TO CHANGES PSYCHOLOGICAL PARTURITION PARTURITION PERIOD BASED ON PARITY AND HOW LABOR IN RSUD SAYANG CIANJUR YEAR OF 2018 - rahmawati, naili (Jurnal Ilmu Kesehatan Immanuel, 2018)
The time of parturition or peurperium started after the birth of the placenta is up to 6 weeks (42 days) after, post-birth mothers will experience some changes in either the physical or psychological change change and some adjustments required by the mother. For those who cannot adjust to the psychological disorders-gangguang experience with a variety of syndromes or symptoms (postpartum stress). Figures for the incidence of baby blues or postpartum blues in Asia is quite high and varies between 26-85% and in Indonesia recorded between 50-70%. This research aims to know the mother's psychological response to changes psychological parturition parturition period based on parity and how childbirth in RSUD SayangÂ  Cianjur year of 2018. Design research is descriptive research with cross sectional approach. The population in this research is the whole mom how can parturition spaces that are located in RSUD Sayang Cianjur while samples in this research was the mother of childbirth that is willing to be respondents and willing to fill out a questionnaire that has researchers prepare as many as 50 person. Data collection is done with the interview techniques using a questionnaire.Research results are obtained on the basis of parity that is as much as 15 people (60.0%), parturition multipara mother gave a positive response and as many as 14 people (56.0%), parturition primipara mother gave a negative response. For research results based on how labor i.e. as many as 12 people (60.0%), parturition maternity mother spontaneously give a positive response and as many as 16 people (53.3%) of mothers whose maternity parturition with action.Â Key words : psychological response, mother childbirth